Thrusting and Orogenesis: The Himalayan Front in central Nepal - Bashyal, Ramesh; Delcaillau, Bernard; Herail, Gerard; Mascle, Georges (Journal of Nepal Geological Society, 1989)
In central Nepal, the Siwalik front represents the southernmost and younger thrust zone of the Himalayas. Here the detrital Mio-Pleistocene Siwalik Formations overthrust the Gangetic Quaternary. The morphostructural organization depends on lateral variations of the tectonic environment. Two main types are characterized. Escarped fronts (400 to 600 m. of relative altitude) coincide with steeply dipping structures, strong morphology resulting from a thrust ramp; immediately to the south the Terai alluvium are folded in relation with a blind thrust. The smoothed fronts (100 to 300 m) correspond to a flat lying thrust. This regional example allows to propose a geodynamic evolutionary model for a foreland thrust front. During the flat thrust motion, thickening and erosion are balanced (smoothed front). In the following time, the southward propagation of the deformation with addition of new units, results in the formation of a frontal ramp which induces a steepening of the structures. The rate of uplift is not compensated by erosion (escarped front).